Indication of social buffering in disbudded calves - Bučková, Katarína; Moravcsíková, Ágnes; Šárová, Radka; Rajmon, Radko; Špinka, Marek (Scientific reports, 2022)
Most dairy calves are housed individually in early ontogeny but social housing has positive effects on calf welfare including an advantage of social buffering, i.e., when negative effects of stress are mitigated through social support of conspecific. The effects of social buffering has not yet been examined in relation to disbudding; a painful husbandry procedure commonly performed on young dairy calves. The objective of this study was to investigate the effect of pair versus individual housing on calves' behavioral reaction to disbudding. In total 52 female calves were randomly allocated either to individual (n = 16) or pair housing (n = 36, 18 focal). Calves were hot-iron disbudded with a local anesthetic and their spontaneous behavior in home pens was recorded for 24 h pre- and post-disbudding. Eating forage, ruminating, resting, exploration, play, self-grooming, and pain-related behaviors were quantified during eight 20 min intervals during the 24 h periods pre- as well as post-disbudding. In pair-housed (PAIR) calves social resting, active and passive allo-grooming were additionally recorded. The differences between individually housed (INDI, n = 10) and PAIR calves (n = 12) were tested by general linear models. The changes in pre- and post-disbudding behaviors in all calves as well as in social behaviors of PAIR calves were tested by paired t-test. We found that head shaking (t = - 3.46, P = 0.0024), head rubbing (t = 4.96, P < 0.0001) and self-grooming (t = 2.11, P = 0.04) increased in all calves after disbudding. Eating forage increased only in PAIR calves (t = 2.50, P = 0.030) which also resulted in a difference between treatments with PAIR calves fed more often than INDI calves (F1,18 = 12.96, P = 0.002). Differences in eating forage may be an indication of improved ability of PAIR calves to recover from disbudding. No other significant differences were detected between treatment groups which might have been caused by our limited sample. Our results provide the first evidence that housing treatment affects calves' reactions to disbudding, with possible indication of social buffering.
Keywords: lokální anestezie; rohy; Anesthesia, Local; Pain; ženské pohlaví; zvířata; Anesthetics, Local; anestetika lokální; Female; Horns; skot; bolest; Eating; přijímání potravy; Cattle; Animals